2017
DOI: 10.1002/jbm.b.34027
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of a calcified cartilage connecting zone by GDF‐5‐augmented fibrin hydrogel in a novel layered ectopic in vivo model

Abstract: Tissue engineering approaches for reconstructing full-depth cartilage defects need to comprise a zone of calcified cartilage to tightly anchor cartilage constructs into the subchondral bone. Here, we investigated whether growth and differentiation factor-5-(GDF-5)-augmented fibrin hydrogel can induce a calcified cartilage-layer in vitro that seamlessly connects cartilage-relevant biomaterials with bone tissue. Human bone marrow stromal cells (BMSCs) were embedded in fibrin hydrogel and subjected to chondrogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
(104 reference statements)
1
8
0
Order By: Relevance
“…Strong staining of SAOS-2 cells embedded in fibrin hydrogel to allow identical processing, confirmed a positive MEF2C, RUNX3, and RUNX2 staining (Supplementary Figure S2C). This underlined the main findings of Western blots and demonstrated that mainly peripheral MPCs underwent hypertrophy, which is in line with peripheral detection of ALP activity (Supplementary Figure S2A) reported before (Dickhut et al, 2009;Fischer et al, 2010;Mueller et al, 2013;Diederichs et al, 2017). In conclusion, specific microenvironmental conditions like higher oxygen and/or better FIGURE 2 | Characterization of MPC and AC differentiation.…”
Section: Upregulation Of Runx3 and Mef2c With Hypertrophy During Mpc supporting
confidence: 85%
“…Strong staining of SAOS-2 cells embedded in fibrin hydrogel to allow identical processing, confirmed a positive MEF2C, RUNX3, and RUNX2 staining (Supplementary Figure S2C). This underlined the main findings of Western blots and demonstrated that mainly peripheral MPCs underwent hypertrophy, which is in line with peripheral detection of ALP activity (Supplementary Figure S2A) reported before (Dickhut et al, 2009;Fischer et al, 2010;Mueller et al, 2013;Diederichs et al, 2017). In conclusion, specific microenvironmental conditions like higher oxygen and/or better FIGURE 2 | Characterization of MPC and AC differentiation.…”
Section: Upregulation Of Runx3 and Mef2c With Hypertrophy During Mpc supporting
confidence: 85%
“…The hMSCs encapsulated in the alginate gel without CMGs was used as the control group. The mRNA expressions included Sox-9 [ 23 ], SZP as the superficial zone marker [ 25 ], Col II, and AGC as the middle zone markers [ 26 ], and Col X and ALP as markers of cartilage hypertrophy in the calcified zone of articular cartilage [ 27 ]. For all markers and culture times, the expressions for aCMG-MSCs and fCMG-MSCs were higher than the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The control group in exhibit A was MSCs encapsulated directly, without CMPs, in alginate. Chondrogenic markers included Sox-9 [37], SZP as the superficial zone marker [39], Col II and AGC as the middle zone markers [16], and Col X and ALP as calcified zone markers [40]. For all markers and incubation times, adult or fetal CMP-MSCs showed higher expressions compared to directly encapsulated MSCs in alginate.…”
Section: Figurementioning
confidence: 97%